THE RELATIONSHIP OF MULTIPLE ROLE CONFLICT AND JOB STRESS THROUGH WORK MOTIVATION AS AN INTERVENING VARIABLE ON PERFORMANCE IN FEMALE EMPLOYEES AT MITRA MEDIKA BANDAR KLIPPA HOSPITAL - Muhammad Zikri Atthariq Daulay; Nazaruddin; Iskandarini (CV. Radja Publika, 2023)
Based on the results of research and discussions that have been carried out previously, it can be concluded as follows: Multiple Role Conflict has a positive and significant effect on Work Motivationon Female Employees at Mitra Medika Bandar Klippa Hospital. Multiple Role Conflict has a positive and significant effect on Performanceon Female Employees at Mitra Medika Bandar Klippa Hospital. Job Stress has a positive and significant effect on Work Motivationon Female Employees at Mitra Medika Bandar Klippa Hospital. Job Stress has a positive and significant effect on Performanceon Female Employees at Mitra Medika Bandar Klippa Hospital. Work Motivation has a positive and significant effect on Performanceon Female Employees at Mitra Medika Bandar Klippa Hospital. Multiple Role Conflict has a positive and significant effect on Performance through Work Motivationon Female Employees at Mitra Medika Bandar Klippa Hospital. Job Stress has a positive and significant effect on Performance through Work Motivationon Female Employees at Mitra Medika Bandar Klippa Hospital.